The Relationship between Resiliency, Psychological Well-being and Marital Satisfaction of Infertile Couples Undergoing in Vitro Fertilization - Esmat Danesh; Parisa Aminalroayaei; Roghieh NooriPour-Liavoli (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objectives: Today infertility problem become social concern and is associated with numerous psychological and social problems. The study sought to determine relationship between levels of resiliency and psychological well-being and marital satisfaction in infertile couples undergoing intrauterine insemination. Material and Methods: Method of research was cross correlational that statistical population comprises all infertile couples who referred to infertility clinic in Karaj city that were 60 couples in 2012-2013. 45 couples between 25-44 years old were selected during 5 months by purposive sampling method. Tools were connor-davidson'sresiliency scale, ryff's psychological well-being questionnaire and hudson's marital satisfaction. data were analyzed by using multiple regression analysis. Results: The results showed that the relationship between Resiliency (β=0.196, P=0.016) and psychological well-being with marital satisfaction in infertile couples (β=0.291, P=0.002) is positive and signifiant and Resiliency and psychological well-being can explain 47% of variance in marital satisfaction (P>0.001). Conclusion: The study showed resiliency with psychological well-being and marital satisfaction affected on mental structure and interpersonal relationships in infertile couple's. Hence measures, including education for promoting the resiliency personality, mental health infertile couples to improve their family relationships provide continuity and context.